Nível tecnológico e fatores de decisão para adoção de tecnologia de produção de caju no Estado do Ceará - Lima, Sergiany da Silva (2008)
The use of appropriate technology in agricultural activity is essantial for better utilization of the productive potential of crops. The cashew represents an important source of employment generation and income for the semi-arid northeastern especially for the Ceará state. However, the explitation of this crop there is still performed with little technology, what causes a negative effect on productivity and the utlizatos of production. Thus, this study aimed to describe the process of technological adoption in crop eashew of Ceará, by the analysis of the socieconomic conditions of producers, and the technological level employee in cajucultura. To that, it was realized a tabulation of the information concerning the farmers economic and social conditions, while the adoption of technology was based on indexes IGM and IGMs. In addition, were estimated the coefficients of the variables of influence on the probability of the technological adoption by the regression function Combined Logistic Distribution Pattern (Logit). The results indicated as the main deficiency of the production system the lack of irrigatin methods, as well preventives controls and treatments of pests and diseases, showing indices considered insufficient for the development of crop cashew. The technologies with the highest levels of adoption were: Harvest and management in the segment cashew for juice, harvest and selection of seedlings in the segment in nature cashew, and management in the nut exploration. The IGM showed that the areas occupied by the in nature cashew has the best tecnology level, using the recommended 46,7%, while those occupied with cashew for nuts and juice usse only 36,4% and 30<1$, respectively, of the technology recommended. Based on IGMs the technological level of crop cashew empoyee in the three segments analyzed (in nature, juice asn nuts) was 35,4%, considered compatible to the activity. The size of the areas planted with giant and dwarf cashew, the acess to credit, the crop cashew as the main activity, farmrs associations and the price of nuts and the peduncle were the amin factors decision of for adoption of technologies in crop cashew in Ceará. Of these factos, only the area planted with giant cashew affects negatively the probability of technologt adoption, while preces of nut and the peduncle were defined as those with greater influence on the probability of technology adoption.